A Study on the Binary and Ternary CuZnAl Catalysts without Additives for Efficient CO Hydrogenation to Ethanol. Issue 8 (4th March 2022) - Liu, Jing; Fan, Jinchuan; Li, Fang; Gong, Jie; Wang, Sen; Yang, Denghui; Huang, Wei
Abstract: Synthesis of ethanol from syngas on CuZnAl catalyst without additives has attracted substantial interest. However, the active sites and the reaction mechanism are still not fully understood due to the complexity of the ternary system. Herein, a series of binary (CuZn, CuAl, ZnAl) and ternary CuZnAl catalysts were prepared using complete liquid method for CO hydrogenation to ethanol. The results show that CAT‐CZ and CAT‐ZA possess much higher ability for ethanol synthesis than CAT‐CA, which is attributed to the presence of the key species Zn and the strong interaction at the interface. In situ DRIFTS measurements reveal the intermediate species of each catalyst, indicating that there are different carbon chain growth paths in CAT‐CZ and CAT‐ZA. The desirable catalytic CO hydrogenation performance (10.87 % of CO conversion and 57.18 % proportion of ethanol in total alcohol) on CAT‐CZA can be attributed the existence of multiple mechanisms for the ethanol production process. Abstract : Key species : CAT‐CZ and CAT‐ZA possess much higher ability for ethanol synthesis than CAT‐CA, which is attributed to the presence of the key species Zn and the strong interaction at the interface. The desirable catalytic on CAT‐CZA can be attributed the existence of multiple mechanisms for the ethanol production process.